A Simple and Rapid HPLC-PDA MS Method for the Profiling of Citrus Peels and Traditional Italian Liquors - Guccione, Clizia; Bergonzi, Maria Camilla; Piazzini, Vieri; Bilia, Anna Rita (Planta Medica, 2016)
A chromatographic method for the qualitative and quantitative characterization of peels and preparations based on different species of Citrus was developed in order to obtain a complete profile of the constituents, including flavonoids and protoalkaloids. Commercial peels of sweet orange, lemon, mandarin, and grapefruit were analyzed. Seventeen constituents including flavanones, flavones, polymethoxyflavones, and protoalkaloids were identified by HPLC-PDA, HPLC-MS, and HPLC-MS/MS using a comparison of retention times and UV-Vis and MS spectra with reference standards and literature data. The total amount of flavanones [neoeriocitrin (5), naringin (8) and hesperidin (9)] and polymethoxflavones [sinensetin (12), nobiletin (14), 3,5,6,7,8,3′,4′-heptamethoxyflavone (15), and tangeretin (16)] was determined and expressed as naringin (8) or hesperidin (9), and sinensetin (12), respectively. The protoalkaloid synephrine was detected in all samples, except in grapefruit, but its content was lower than the limit of quantification. Qualitative and quantitative chemical profiles of three different Italian aromatic liquors (“Limoncello”, “Arancello”, and “Mandarinetto”), prepared according to traditional recipes, were also analyzed.
Keywords: Citrus peels and preparations; flavanones; flavones; polymethoxyflavones; protoalkaloids; HPLC-PDA MS